Assess the Elements that Influence Compassion Fatigue in Nurses - Mubarak Musalam Khlaf Alrashedi; Saud Nasser Fayz Alzarea; Abdulaziz Gaied Rashid Alharbi; Naif Sultan Thuwaini Alshammari; Bandr Mohammed Algafidi; Sultan Meshal Oways Alotaibi; Khalid Sayah Hulayfan Alharbi; Basim Sulaiman Abdullah Alkhudhayri; Abdulaziz Abdullah Jazaa Alruways; Majed Bin Hamad Bin Salem Alhulayyil (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Compassion fatigue, described as the physical, emotional, and psychological exhaustion stemming from caregiving demands, is prevalent among nurses, particularly in high-stress settings such as obstetrics and gynecology. Despite its profound impact on nurses’ well-being and patient care quality, factors contributing to compassion fatigue remain underexplored. This study investigates the prevalence of compassion fatigue among nurses and examines its associated factors, including burnout, emotional labor, and social support. Methods: A cross-sectional survey was conducted among 311 nurses working in obstetrics and gynecology units at tertiary hospitals. Validated instruments were used to measure compassion fatigue, burnout (Maslach Burnout Inventory), emotional labor, and social support. Data were analyzed using descriptive statistics, correlation analysis, and stepwise multiple linear regression. Mediation analysis explored the role of social support in mitigating compassion fatigue. Results: Nurses reported moderate levels of compassion fatigue (mean = 3.4, SD = 0.7) and burnout (mean = 3.2, SD = 0.8). Emotional labor was significantly high (mean = 4.1, SD = 0.6), while perceived social support was moderate to high (mean = 48.3, SD = 7.2). Compassion fatigue was positively correlated with burnout (r = 0.71, p < 0.001) and emotional labor (r = 0.65, p < 0.001), and negatively correlated with social support (r = -0.52, p < 0.001). Burnout and emotional labor emerged as significant predictors of compassion fatigue, with social support demonstrating a mitigating effect. Conclusion: Compassion fatigue among nurses in obstetrics and gynecology is significantly influenced by burnout and emotional labor, while social support serves as a protective factor. Interventions targeting emotional resource management and fostering supportive work environments are critical for reducing compassion fatigue and enhancing nurse well-being and patient care quality.